INTEGRASI NILAI-NILAI SYARIAH DALAM MODEL PERCEIVED VALUE: KERANGKA KONSEPTUAL UNTUK PEMASARAN PRODUK HALAL - Rahmah, Nur (IAIN Kendari, 2024)
In an increasingly competitive era, companies must integrate Islamic values into the perceived value model to provide added value to customers through quality services, thereby winning the competition in the halal product market. This study aims to analyze the integration of Islamic values into perceived value in halal product marketing. The research focuses on conceptual analysis using qualitative research methods and secondary data sources by reviewing relevant literature on the main topic of the study. The findings indicate that the application of perceived value to halal products can enhance trust and purchase intention among Muslim consumers, where the halal label serves as an extrinsic information cue that improves the shopping experience and provides a competitive advantage for companies in building loyalty and long-term relationships with Muslim customers, while ensuring product compliance with Islamic principles. The implication is that the integration of Islamic values into the perceived value model enhances the trust and purchase intention of Muslim consumers, as well as provides a competitive advantage for companies in building customer loyalty in the halal product market.